The Effect of SF3B1 Mutation on the DNA Damage Response and Nonsense-Mediated mRNA Decay in Cancer - Leeksma, Alexander C.; Derks, Ingrid A. M.; Kasem, M. Haidar; Kilic, Emine; de Klein, Annelies; Jager, Martine J.; van de Loosdrecht, Arjan A.; Jansen, Joop H.; Navrkalova, Veronika; Faber, Laura M.; Zaborsky, Nadja; Egle, Alexander; et al. (Frontiers in Oncology, 2021)
Recurrent mutations in splicing factor 3B subunit 1 (SF3B1) have been identified in several malignancies and are associated with an increased expression of 3’ cryptic transcripts as a result of alternative branchpoint recognition. A large fraction of cryptic transcripts associated with SF3B1 mutations is expected to be sensitive for RNA degradation via nonsense-mediated mRNA decay (NMD). Several studies indicated alterations in various signaling pathways in SF3B1-mutated cells, including an impaired DNA damage response (DDR) in chronic lymphocytic leukemia (CLL). In this study, we investigated isogenic cell lines and treatment naïve primary CLL samples without any TP53 and/or ATM defect, and found no significant effects of SF3B1 mutations on the p53/ATM response, phosphorylation of H2AX and sensitivity to fludarabine. Cryptic transcripts associated with SF3B1 mutation status were observed at relatively low levels compared to the canonical transcripts and were validated as target for mRNA degradation via NMD. Expression of cryptic transcripts increased after NMD inhibition. In conclusion, our results confirm involvement of NMD in the biological effects of SF3B1 mutations. Further studies may elucidate whether SF3B1-mutant patients could benefit from NMD modulatory agents.